The Hybrid Practitioner Building, Teaching, Researching Architecture - Voet, Caroline; Schreurs, Eireen; Thomas, Helen (Leuven University Press, 2022)
The practice of architecture manifests in myriad forms and engagements. Overcoming false divides, this volume frames the fertile relationship between the cultural and scholarly production of academia and the process of designing and building in the material world. It proposes the concept of the hybrid practitioner, who bridges the gap between academia and practice by considering how different aspects of architectural practice, theory, and history intersect, opening up a fascinating array of possibilities for an active engagement with the present. The book explores different, interrelated roles for practicing architects and researchers, from the reproductive activities of teaching, consulting and publishing, through the reflective activities of drawing and writing, to the practice of building. The notion of the hybrid practitioner will appeal strongly to students, teachers and architectural practitioners as part of a multifaceted professional environment. By connecting academic interests with those of the professional realm, The Hybrid Practitioner addresses a wider readership embracing landscape design, art theory and aesthetics, European history, and the history and sociology of professions.